Efektifitas Kombinasi Ekstrak Sambiloto (Andrographis paniculata (burm.f.) nees) dan Daun Salam (Syzygium polyanthum (wight) walp) terhadap Kadar hs-CRP pada Pasien Dislipidemia - Yulindaa, Wina; Lindarto, Dharma; Syafril, Santi (Majalah Kedokteran Nusantara The Journal Of Medical School, 2017)
Introduction Dyslipidemia is risk factor of cardiovascular disease and significantly correlated with increased hs-CRP concentration. Simvastatin, a sintetic antidyslipidemic drug, decreases hs- CRP concentration. But long term use of sintetic drug may cause side effects, so that phytopharmaca is preferably to be consumed. Combination sambiloto extract and salam could decrease proinflammatory cytokines, cholesterol, and triglyceride. Aim of this study was to compare the effect of combination sambiloto extract and salam with simvastatin on hs-CRP concentration in dyslipidemic patientsMethods This clinical trial use prospective design. Treated group (n = 15) and control group (n = 15) were selected by double blind random sampling. Before and after 30 days therapy, blood sample was taken. Data was analysed with SPSS, p < 0.05 was considered significant.Results There was significant decrease of hs-CRP before and after 30 days therapy in treated group ((3.02 ± 3.13 vs 1.67 + 1.37) mg/dL; p = 0.005); meanwhile insignificant decrease was there in control group ((2.78 ± 1.97 vs 2.25 ± 2.32) mg/dL; p = 0.285). hs-CRP decrease of treated group was bigger than in control group, but statistically insignificant ((1.35 ± 2.37 vs 0.53 ± 1.96) mg/dL; p = 0.089 mg/dL).Conclusion Combination sambiloto extract (Andrographis paniculata) and salam (Syzygium polyanthum) 2 x 150 mg for 30 days decreased hs-CRP concentration lower than simvastatin 1 x 20 mg, but statistically insignificant.Keywords : hs-CRP, Andrographis paniculata and Syzygium polyanthum, dyslipidemia